CURRENT TRENDS AND BASIC METHODS OF RAW DATA INTELLIGENT ANALYSIS (Transport systems and technologies, 2018)
Fundamental methods of the data mining, such as visualization and statistical methods, artificial intelligence, decision trees and genetic algorithm are considered. Fields oftheir possible application in the task of railroad power supply system intellectualization are research.
Keywords: intelligent information processing, data mining, electricity, railways